Managing the Local TV in East Java Service Area, Indonesia: Focus on Strategic Triangle - Surokim As (Communication Sphere, 2015)
ABSTRACTLocal TV in Indonesia faced complex problems and challenges. Broadcast manager hasto do professionally focusing on three strategic aspects. Those are institutional / business,program / broadcast content, and technical / technology. In the aspect of business, local TV ismanaged not only to reach the local market, but also regionally and internationally in order toobtain more profits in the business. In the aspect of the program content, manager shouldexplore locally content combining to global and popular program. This glocalization programcan reach more viewer. In the technological aspects, the local TV manager must be familiar andadopted the latest broadcast technology, including digital and convergence of newtechnologies. Local TV can adapt and develop technologies for improving the quality ofbroadcast reception and service.Keywords: Local TV, Content Program, Institutional-Business, Technology, East Java